Parents' Reasons for Sending Their Child to Montessori Schools - Elisabeth Hiles (University of Kansas, 2018)
Although the Montessori Method of education is more than 100 years old, the number of Montessori schools in the United States has exponentially increased since 1990. Montessori methods and practices can be complex and difficult for parents to understand, even among parents whose child attends Montessori schools. Moreover, it is unclear why parents decide to enroll their child in Montessori schools. This study presents the results of a survey administered to 124 parents whose children were enrolled in 3 Montessori schools in Massachusetts. Findings indicate that 4 reasons motivated parents' choice of Montessori education: attraction to Montessori principles, perceived fit with the Montessori philosophy or school, anticipated outcomes, and attraction to the Montessori classroom. These findings indicate that, to support parents' decision-making, Montessori administrators should invest in parental and public awareness about Montessori education and provide prospective families with specific information related to school fit, classroom environment, and long-term student outcomes.